La adaptación del politainment a YouTube: el uso de los partidos políticos españoles durante la campaña electoral de abril de 2019 - D. Mario Daniel TAMAYO SANZ,Dra. Marta REBOLLEDO DE LA CALLE,Dr. Javier SERRANO PUCHE, (Fonseca, Journal of Communication, 2023)
Politainment is a concept that describes the progressive adaptation of political and media actors to the logic of entertainment culture. This phenomenon has been extensively studied in the medium in which it was born, television; however, as digital platforms gain greater prominence as a source of political information, politainment finds in them a new space in which to develop